Validating the Motives for Online Gaming Questionnaire (MOGQ) within the WHO and APA gaming disorder symptoms frameworks - Christian Bäcklund; Daniel Eriksson Sörman; Hanna M. Gavelin; Zsolt Demetrovics; Orsolya Király; Jessica K. Ljungberg (Computers in Human Behavior Reports)
The increasing interest in digital games and the reasons behind their popularity worldwide warrants further psychometric investigation of motivation factors for engagement in digital games. The present study aimed to validate the Motives for Online Gaming Questionnaire (MOGQ) in a Swedish sample and compare the associations between the seven motivational factors and gaming disorder symptoms across the American Psychiatric Association and World Health Organization diagnostic frameworks. Furthermore, considering the utility of more concise psychological measures, a 14-item version of the MOGQ was developed (MOGQ-14). A sample of 678 Swedish video game players (68.4% men, 29.7% women, and 1.9% other, Mage = 29.5 years, range 15–66) were included in the analyses after participating in an online survey. The analyses revealed that the Swedish version of the MOGQ had good psychometric properties. All MOGQ factors showed good reliability (McDonald's omega), and all intercorrelations among the MOGQ dimensions were consistent with previous findings. The results showed that, on average, men reported higher gaming motivations concerning competition than women. The relationships between six gaming motivation factors (social, escape, competition, coping, skill development, fantasy) and gaming disorder symptoms were consistent with previous research. Findings indicated that the relationship between motivations (escape and recreation) and gaming disorder symptoms varied across APA and WHO diagnostic frameworks, depending on the motivation scale used (MOGQ or MOGQ-14). Recreation significantly differed in its relationship with symptoms when using MOGQ, and the MOGQ-14 showed larger effect sizes in the WHO framework for escape and recreation motivations.